Safety and nutritional value of a dried killed bacterial biomass from Escherichia coli (FERM BP‐10942) (PT73 (TM)) as a feed material for pigs, ruminants and salmonids. (30th August 2017) - ,; Rychen, Guido; Aquilina, Gabriele; Azimonti, Giovanna; Bampidis, Vasileios; Bastos, Maria de Lourdes; Bories, Georges; Cocconcelli, Pier Sandro; Flachowsky, Gerhard; Gropp, Jürgen; Kolar, Boris; Kouba, Maryline; et al.
Abstract: PT73 (TM) is a dried, heat‐inactivated bacterial biomass used as a feed material produced from an Escherichia coli K‐12 strain, which was genetically modified to overproduce threonine. The recipient organism E. coli MG 1655 is considered to be safe. The traits introduced in the final modified strain E. coli FERM BP‐10942 are mainly limited to the overproduction of threonine. No full‐length antibiotic resistance genes or other sequences of concern remain in the modified strain. In conclusion, the EFSA Panel on Additives and Products or Substances used in Animal Feed (FEEDAP): does not identify risks for human and animal health or the environment from this biomass regarding the genetic modification of the strain. The proposed recommended use level for dairy cows (8% PT73 (TM) of feed dry matter ( 7% in complete feed)) and salmonids (13%) is considered safe for these target animals. The conclusion form dairy cows could be extended to other ruminants (from the beginning of rumination). Complete feed for pigs for fattening may contain up to 10% PT73 (TM). The toxicological data indicate effects of PT73 (TM) on blood coagulation and liver, which are considered to be adverse. As a consequence, the FEEDAP Panel is unable to conclude on the safety for the consumer of products derived from animals receiving feed containing PT73 (TM). PT73 (TM) is not considered a skin/eye irritant but should be considered as a potential skin and respiratory sensitiser. Moreover, any exposure of users to dust from the product via the inhalation route should be considered a serious risk. The FEEDAP Panel considers that substitution of PT73 (TM) for other protein‐rich feed materials will not adversely affect the environment.